Analisis manfaat public relation di bagian keuangan PPTQ Baitul Ghonni - Rohim, M. (Maliki Interdisciplinary Journal, 2023)
This research aims to understand the benefits of Public Relations (PR) in community services in the financial section of the Baitul Ghonni Tahfidzul Qur'an Islamic Boarding School (PPTQ). The research method used is qualitative with a literature review approach and direct observation of the Islamic boarding school's financial department. Observation results show that Public Relations in the financial sector has significant benefits, including building public trust, providing satisfaction, and forming a positive image. The Islamic boarding school treasurer acts as a trustee and is able to provide satisfactory service through friendly communication and good service quality. It can be concluded that the role of Public Relations has an important impact in strengthening relations between Islamic boarding schools and their communities, as well as in building a positive reputation in the eyes of the community. Thus, the use of Public Relations in Islamic boarding schools can be an effective strategy in strengthening social interactions and improving the quality of public services.